The Other Population Crisis What Governments Can Do about Falling Birth Rates - Kramer, Steven Philip (Johns Hopkins University Press, 2014)
In many developed countries, population decline poses economic and social strains and may even threaten national security. Through historical-political case studies of Sweden, France, Italy, Japan, and Singapore, The Other Population Crisis explores the motivations, politics, programming, and consequences of national efforts to promote births. Steven Philip Kramer finds a significant government role in stopping declines in birth rates. Sweden's and France's pro-natalist programs, which have succeeded, share the characteristics of being universal, not means-tested, and based on gender equality and making it easy for women to balance work and family. The programs in Italy, Japan, and Singapore, which have failed so far, have not devoted sufficient resources consistently enough to make a difference and do not support gender equality and women's work-family balance, Kramer finds.